1998
DOI: 10.1017/s0266467498000327
|View full text |Cite
|
Sign up to set email alerts
|

The soft scale (Coccidae) associates of Malaysian ant-plants

Abstract: Myrmecophytic species of the Paleotropical plant genus Macaranga (Euphorbiaceae) have hollow stems that are almost always occupied by ants of the genus Crematogaster and scale insects of the family Coccidae (Hemiptera: Coccoidea). The coccids have a cryptic endophytic lifestyle and are confined to this microhabitat. They are much more diverse than previously recognised. First data are presented on the diversity, prevalence, specificity and distribution of the coccids associated with myrmecophytic Macaranga spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 24 publications
2
67
1
1
Order By: Relevance
“…The limited range of symbiotic hemipteran species of Macaranga plant-ants (Heckroth et al 1998;Ueda et al 2008Ueda et al , 2010 can no doubt be maintained by such rejecting behaviors as observed in our system. Selection of scale insects by plant-ants may be adjusted in the evolutionary process on the basis not only of food intake from the honeydew or meat of scale insects but also of the total effects, including herbivory damage caused by the scale insects on the host plants.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The limited range of symbiotic hemipteran species of Macaranga plant-ants (Heckroth et al 1998;Ueda et al 2008Ueda et al , 2010 can no doubt be maintained by such rejecting behaviors as observed in our system. Selection of scale insects by plant-ants may be adjusted in the evolutionary process on the basis not only of food intake from the honeydew or meat of scale insects but also of the total effects, including herbivory damage caused by the scale insects on the host plants.…”
Section: Discussionsupporting
confidence: 50%
“…However, partnerships between plant-ants and coccids are not highly species-specific, although several Coccus spp. exclusively inhabit ant nests in Macaranga myrmecophytes (Heckroth et al 1998;Ueda et al 2008Ueda et al , 2010.…”
Section: Study Area and Macaranga Myrmecophytesmentioning
confidence: 99%
See 2 more Smart Citations
“…most Cladomyrma ants; Moog et al 2003), whereas a few others only cultivate coccids (e.g. ants of the genus Crematogaster Lund in the hollow stems of Macaranga Thouars; Heckroth et al 1998). In the Neotropics, the coccids most frequently associated with specialist plant-ants, or with other ants nesting inside plant cavities, belong to the genera Akermes Cockerell, Cryptostigma Ferris, Cyclolecanium Morrison, Megasaissetia Cockerell, Neolecanium Parrott and Toumeyella Cockerell of the subfamily Myzolecaniinae (Hodgson 1994.…”
mentioning
confidence: 99%